Kebahagiaan Spiritual bagi Nestapa Manusia Modern (Studi Pemikiran M. Quraish Shihab dalam Tafsîr Al-Mishbâh̲) - Muhammad Sholhan Mansyur; Kerwanto Kerwanto; Muh. Adlan Nawawi (STIKes Ibnu Sina Ajibarang, 2023)
Human misery affected by modernization that led to a spiritual crisis. As a result they experience stress, depression and mental pressure because their spiritual needs are rarely or even never met. In the end, they do not feel the tranquility, order and happiness of life. The purpose of this study is to find and explain the spiritual happiness of M Quraish Shihab perspective in Tafseer Al-Mishbâh and find and explain the solution of Tafseer Al-Mishbâh in coping with grief in modern humans. The method used in this study is qualitative (library research) by using content analysis and observation. The primary sources used are Tafsîr Al-Mishbâh by M Quraish Shihab and his relevant works. As for secondary sources, they are books that are closely related to the spiritual happiness and sorrow of modern man. The results of this study found that there are three terms of happiness that are considered relevant and representative, namely falâh, fauz and ithmaanna and choose some verses from the three terms, some indicators that are very helpful to the creation of spiritual happiness. These indicators are: religiosity, patience, altruism, carrying out obligations in Islamic law, leaving prohibitions in Islamic law. All of these indicators are also considered very relevant to deal with the grief of modern humans, especially the problem of spiritual crisis that they face so that stress, depression, anxiety, anxiety arise. This study implies that to achieve happiness in life, the only way is to draw closer to God, rely on him, by carrying out all His commandments and avoiding all his prohibitions